Optical temperature sensing of up-conversion luminescent materials: Fundamentals and progress - Zhao, Yan; Wang, Xusheng; Zhang, Ying; Li, Yanxia; Yao, Xi (Journal of alloys and compounds, 2020)
Temperature monitoring plays an important role in ensuring product quality, saving energy, promoting the development of national economy and providing basic diagnostic criteria in the field of biomedicine. Due to the importance and universality of temperature measurement, the study of temperature sensing property and the pursuit of high sensitivity have become an important research field of rare-earth luminescent materials in recent years, and have received extensive attention. In this paper, different optical temperature sensing methods and principles, the application of rare-earth luminescent materials in optical temperature sensing, and the types of up-conversion luminescent thermometry materials are reviewed. First, we introduce that optical thermometry can realize non-contact temperature measurement, large-scale imaging, wide dynamic range and rapid response in biological fluorescent tag, accurate measurement of local temperature in medical treatment, and direct temperature measurement of an inaccessible object, which has a very broad application prospect. Meanwhile, we emphasize that the fluorescence intensity ratio technique based on the thermally coupled levels of rare-earth ions has been considered as a reliable and promising non-contact optical temperature sensing method due to its high accuracy and reliability. In the later sections, we review the fundamentals and research progress of rare-earth luminescent materials in optical temperature sensing. Double-doped up-conversion thermometry materials with diverse activators and Yb3+ as sensitizers are mainly introduced, as well as tri-doped multi-color optical thermometry materials. Finally, we summarize the current research results and discuss further research directions on the basis of their current developments. It is hoped that this review could provide new inspiration for the subsequent novel temperature sensors in the future. •Optical thermometry of up-conversion luminescent material is reviewed emphatically.•Optical thermometry focuses on the fluorescence intensity ratio method.•The main challenges that we need to overcome are discussed.